Kesalehan Pragmatis dan Kesalehan Etis: (Pergulatan Eksistensial Guru dalam Globalisasi Pendidikan) - Sutikno, Sutikno (rogram Studi Pendidikan Guru Madrasah Ibtidaiyah (PGMI) Fakultas Tarbiyah dan Ilmu Keguruan Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH) Lamongan, 2023)
This article focuses on the teachers existential battle in the contemporary educational globalization especially Islamic education which is faced to the aspects of ethical piety and pragmatical piety values. This piety just not as given identity but is founded on consciousness and reason structures of the teachers. This piety creates and implicates risk and consequence for the process of teacher existencialism and future of Islamic education. An attempt to Islamic principles and values on the essence of teacher become an alternative resolution in order to escape from existencial ambivalence and ambiguity in the process of educational globalizations. Those Islamic priciples and values in the origins of Islamic history and traditions able to become rational and trancendental paradigm in the modern and postmodern times.